Selinexor in relapsed/refractory multiple myeloma. (June 2020) - Richter, Joshua; Madduri, Deepu; Richard, Shambavi; Chari, Ajai
Multiple myeloma (MM) represents an incurable hematologic malignancy. Despite significant advances over the past decade, with the advent of multiple new classes of anti-myeloma agents, including immunomodulatory drugs, proteasome inhibitors and monoclonal antibodies, patients ultimately relapse. Selinexor is a first-in-class exportin-1 inhibitor with activity in these multiply relapsed and refractory patients. Although the current Food and Drug Administration (FDA) approval is for the doublet of Selinexor in combination with dexamethasone, ongoing clinical trials are evaluating a number of combination regimens. These triplet and quadruplet, selinexor-based, regimens are showing significant activity in "triple-class" refractory patients. With appropriate combination drug choice, drug dosing, and supportive measures, patients with previously no viable options for therapy, now have multiple potential regimens to control their disease.